Avaliação da qualidade de vida no trabalho na percepção dos funcionários: um estudo de caso numa empresa prestadora de serviço de eletricidade - Machado, Janíscea Keylla Mariano (2016)
In the context of changes in the business environment has become competitive, and to achieve quality products and services, workers need to be satisfied with the work. In this sense, the theme quality of life can be a strategic element in the management of human resources, as it can generate its effects on the quality of goods or services produced by organizations. This dissertation approaches this theme aimed at evaluate the quality of working life in the perception of employees of a provider company electricity service. To achieve this objective we used the qualitative and quantitative research whose data were collected from the application of a questionnaire composed of 28 questions to 145 respondents, with reference to the dimensions and variables, the quality of life model at work Walton ( 1975) which contemplates five dimensions: Working Conditions; Growth Opportunity, Security and Organization for Social Integration; Use and Capacity Development, and leisure and entertainment; Preventive Health and Social Relevance of Life at Work; Compensation and Fair and Adequate. The responses of the items of the questionnaire were expressed by Likert scale (1 very dissatisfied, 2 dissatisfied, 3 neither satisfied nor dissatisfied, 4 satisfied and 5 very satisfied). For the verification of the results of this research, the data were measured using the method of Exploratory Factor Analysis and analyzed according to each dimension. From factor analysis it was found that the variables corresponding to the factors (dimensions) the greatest impact on QWL, in the perception of employees, were physical and mental well-being, cleanliness and organization, environmental conditions, protective equipment, compliance with rights, career advancement, improvement of knowledge, job recognition, motivation and performance, freedom of expression, performing the activities, job satisfaction, skills and knowledge, autonomy, gymnastics, organization's image, social responsibility, adequate income, equity internal and external equity. The survey results revealed that the majority of workers declared partially satisfied with their quality of working life. In this sense one can say that according to the perception of workers, the level of quality of working life offered by the company is at least good. It was also found that as the mean scores, workers who perform their tasks on the company's external environment had a quality of life assessment in more positive work than those who execute their tasks in the internal environment.